Supply Management Strategic Sourcing - Parniangtong, Sathit (Management for Professionals, 2016)
This book takes a process approach of identifying, evaluating, selecting, managing and developing suppliers to create more value for customers. It begins by outlining the mental shift necessary to build robust relationships with suppliers. Next, the book details strategic sourcing methodology: a step-by-step approach for creating productive relationships with key suppliers, providing illustrations and examples from the author's experience throughout. The third and final part of the book provides details of a comprehensive process developed to arm the negotiation team with all facts necessary to reach desired outcomes. This detailed step-by-step process consists of negotiation strategy and case building, supplier response and positioning, negotiation planning, discussions, and resolution, and supplier evaluation. In addition, the book highlights best practices in strategic sourcing representing tactics for buyers to leverage their buying power to ensure they attain full value. These best practices are drawn from several strategic sourcing projects carried out for leading companies in the USA over several years.